Bone Peg Grafting for Capitellar Osteochondritis Dissecans in Adolescent Baseball Players. Issue 1 (January 2018) - Oshiba, Hiroyuki; Itsubo, Toshiro; Komatsu, Masatoshi; Uchiyama, Shigeharu; Kato, Hiroyuki
Abstract : Background: Capitellar osteochondritis dissecans (OCD) is a focal injury of the articular cartilage involving separation of a segment of cartilage from the subchondral bone that is infrequently encountered in the dominant-side elbow of adolescent throwing athletes1, 2 . The literature suggests that patients may achieve better short and mid-term results when treated with certain types of surgical procedures3, 4 . Selection of the appropriate surgical method should be based on the International Cartilage Repair Society (ICRS) OCD classification system5 . For lesions involving ⩽50% of the surface area of the capitellum, debridement with microfracture and/or loose body removal have shown excellent results. For lesions involving >50% of the surface area of the capitellum and classified as ICRS OCD III or IV, autologous osteochondral grafting may be the most suitable treatment6 -8 . Bone peg grafting (BPG) has been shown to be an effective treatment option for early-stage capitellar OCD that can preserve the local hyaline cartilage9, 10 . Description: Using direct vision and with arthroscopy, the continuity of the capitellar surface and the stability of the capitellar lesion were evaluated according to the ICRS OCD classification5 . BPG was indicated for adolescents with ICRS OCD I or II. The elbow was opened between the extensor carpi ulnaris and the anconeus muscle (Kocher interval). Another skin incision of 3 cm in length was made at the posterior aspect of the metaphysis of the ipsilateral olecranon. Three, 4, or 5 bone pegs of approximately 20 mm in length were harvested from the posterior ulnar cortex. A Kirschner wire of 3 mm in diameter was used for drilling holes in the lesion, and then the bone pegs were inserted with tweezers to a depth of 10 mm. Next, a flat-surfaced rod was placed on the head of each bone peg to press it to a depth slightly lower than the articular cartilage surface. Postoperatively, the elbow was immobilized for 3 weeks. Throwing was allowed at 6 months, and a return to competitive baseball at preinjury levels was permitted at 8 months after BPG. Alternatives: Arthroscopic debridement of the lesion. Arthroscopic bone marrow stimulation or microfracture. Fragment fixation using metal implants or biodegradable materials. Use of autologous osteochondral graft from the distal aspect of the femur or from a rib. Rationale: Our follow-up study after BPG revealed that 10 of 11 patients with ICRS OCD I or II capitellar OCD could return to their preinjury baseball ability and that 8 of the 11 lesions completely healed as seen radiographically11 . Radiographic and magnetic resonance imaging (MRI) findings showed that BPG could secure the lesion to the osseous floor as a physiological scaffold. Fragment fixation with metal implants or biodegradable materials carries a risk of damaging cartilage surfaces, and autologous osteochondral grafting is too invasive for this early-stage lesion. BPG is indicated for ICRS OCD I or II lesions, especially with central positioning and/or occupying <75% of the size of the capitellum in the coronal plane11 .